PENGARUH SUHU NOZZLE 3D PRINTING TERHADAP KEKUATAN TARIK DAN KEKERASAN PERMUKAAN FILAMEN PP DAUR ULANG - Adnan Fatchurrachman; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Scientific Journal of Mechanical Engineering Kinematika, 2026)
This study aims to investigate the effect of nozzle temperature variations on the tensile strength and surface hardness of 3D-printed specimens using polypropylene (PP) filament derived from instant noodle packaging waste. The filament was produced through an extrusion process at 200°C and subsequently printed into test specimens using Fused Deposition Modeling (FDM) with nozzle temperatures of 190°C, 200°C, and 210°C. Tensile testing was conducted in accordance with ASTM D638 Type IV, while hardness testing was performed using the Shore D method. The results show that nozzle temperature significantly affects the mechanical and physical properties of the specimens. The optimum performance was obtained at 200°C, yielding a tensile strength of 16.83 MPa and a hardness of 47.80 Shore D. At 190°C, both tensile strength and hardness decreased, while at 210°C hardness increased but tensile strength declined due to potential thermal degradation. Therefore, 200°C is identified as the optimum temperature, providing the best balance between mechanical performance and structural stability